2012
DOI: 10.1128/jvi.06618-11
|View full text |Cite
|
Sign up to set email alerts
|

Substitutions at Amino Acid Positions 143, 148, and 155 of HIV-1 Integrase Define Distinct Genetic Barriers to Raltegravir Resistance In Vivo

Abstract: Mutations at amino acids 143, 148, and 155 in HIV-1 integrase (IN) define primary resistance pathways in subjects failing raltegravir (RAL)-containing treatments. Although each pathway appears to be genetically distinct, shifts in the predominant resistant virus population have been reported under continued drug pressure. To better understand this dynamic, we characterized the RAL susceptibility of 200 resistant viruses, and we performed sequential clonal analysis for selected cases. Patient viruses containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 26 publications
4
28
0
Order By: Relevance
“…To date, clinical studies demonstrated that three major resistance pathways, Y143C/ H/R, Q148H/K/R, and N155H were frequently observed in patients with virological failure under a RAL-based regimen (19)(20)(21)(22). The N155H mutation was usually accompanied by the secondary mutation L74M, E92Q, T97A, G136R, or V151I (23)(24)(25).…”
mentioning
confidence: 99%
“…To date, clinical studies demonstrated that three major resistance pathways, Y143C/ H/R, Q148H/K/R, and N155H were frequently observed in patients with virological failure under a RAL-based regimen (19)(20)(21)(22). The N155H mutation was usually accompanied by the secondary mutation L74M, E92Q, T97A, G136R, or V151I (23)(24)(25).…”
mentioning
confidence: 99%
“…However, longitudinal evaluations have demonstrated that RAL-resistant viruses with substitutions at position 148 or 155 may be replaced by variants with Y143 substitutions upon continued RAL treatment (25)(26)(27). In a majority of cases, Y143 substitutions comprise C and R, both of which can confer significant reductions in RAL susceptibility (17,18,25,27).…”
mentioning
confidence: 99%
“…In a majority of cases, Y143 substitutions comprise C and R, both of which can confer significant reductions in RAL susceptibility (17,18,25,27). RAL-resistant viruses with Y143H substitutions have also been reported, albeit much less frequently (27,28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, INSTI primary resistance mutants may coexist as distinct subpopulations that evolve over time with or without development of secondary INSTI resistance substitutions (9,31,34). Temporal shifts in resistance pathways from IN-N155H to IN-Q148H/K/R have been observed in patients failing RAL-containing regimens, likely due to the selective advantage of more resistant IN-Q148H/ K/R mutants under continued drug pressure (35)(36)(37)(38). Our data support these findings in the context of EVG, with the less resistant IN-N155H mutant appearing to have a fitness advantage over the IN-Q148R mutant at low EVG concentrations and the reverse occurring at high EVG concentrations.…”
Section: Discussionmentioning
confidence: 99%